Specular affinities: from (self-)reflexivity to intermediality via "mise en abyme" - Chinita, Fátima (2022)
This chapter is a theoretical account of the convergence between cinematic self-reflexivity and intermediality. Agreeing with Petr Szczepanik, who considers that “reflexivity constitutes a fundamental feature of all kinds of intermediality” (2002, 29), I ponder upon their mutual self-constructed and self-revealing nature and the existence of an authorial discourse informed both by a formal and a conceptual makeup. Indeed, mise en abyme, the key figure of artistic specularity, may combine the enunciative surplus of storytelling (whereby intradiegetic creators and spectators are revealed at their activities) with a fictional mirroring of the story itself (Dällenbach, 1977). Known for reinforcing the frame-breaking devices of cinematic reflexivity, "mise en abyme" may also convey the appropriation of other art forms by cinema, either as media transformation or transmediation. Departing from the idea that the arts themselves generate an exchange that invokes the materiality of the media and, hence, the self-reflexive potential of the art forms, I posit that an additional meaning of in-betweeness is in order. Adapting Gilles Deleuze’s theory of the crystal-image (1985) to this intermedial context, I argue in favour of an “intermedia-image,” consisting of a perpetual flux of qualified media in which the "mise en abyme" generates a true constellation of ever new inter-art combinations.